A Primer on Pumping and Dumping: How Hedge Funds Do It and How Others Might Profit - Samsa, Greg (Archives of Business Research, 2021)
Pumping and dumping occurs when the price of a stock is artificially inflated and then drops. Here, we illustrate how hedge funds can accomplish pumping and dumping, and argue why this strategy is likely to be successful for them. We illustrate why writing a short-term in-the-money covered call option might constitute an informed speculation when pumping and dumping is suspected. In contradistinction to the usual practice, estimating the returns of a strategy which is based upon the predictable characteristics of pumping and dumping would be best tested prospectively, and social media communities might fruitfully participate in such research.